Hyperspectral Dark Field and Confocal Raman Microscopy Studies in Chemistry and Nanotechnology - Shinohara, Jorge da Silva (2023)
Hyperspectral imaging can provide accurate information on the distribution of the chemical species in materials and biological samples, based on the analysis of their electronic and vibrational profiles. In special, confocal Raman microscopy is one of the best ways to access the chemical distribution of molecules, especially under resonance Raman or SERS conditions. On the other hand, enhanced dark field optical microscopy can be employed for hyperspectral imaging in the visible and near-IR region, while extending the optical resolution up to the nanoscale dimension. It allows the detection of gold or silver single nanoparticles, as well as spectral monitoring from the characteristic surface plasmon bands. The two hyperspectral microscopies can be conveniently combined to provide nanoscale electronic and vibrational information of the species present in a wide variety of chemical and biological systems. Case studies, including the classical spot-test analysis of nickel(II) ions with dithizone are here reported. A great enhancement of sensitivity in the detection of nickel(II) ions, by at least 4 orders of magnitude, has been observed in this work. Hyperspectral measurements allowed the mapping of the gold nanoparticles (AuNP) distribution on cellulose fibers and on glass, and the evaluation of their extinction and SERS spectra for analytical purposes. Spot tests analysis metal ions with pentacyanidoferrate(II) complexes have also been examined from the point of view of electronic and Raman spectral images. Differentiation of the chemical and electromagnetic mechanisms in the SERS spectra of substituted terpyridine iron(II) complexes with gold nanoparticles has been reported. Characterization of Turkevich nanodisks, and ranelate induced gold nanoparticles formation have also been conducted in this thesis. Finally, hyperspectral techniques have been successfully employed to probe the interaction of gold nanoparticles with microtubules associated with molecular machines.